Lessons Learned from a Single Institution’s Eight Years of Experience with Early Cleft Lip Repair - Idean Roohani; Collean Trotter; Pasha Shakoori; Tayla A. Moshal; Sasha Lasky; Artur Manasyan; Erin M. Wolfe; William P. Magee; Jeffrey A. Hammoudeh (Medicina, 2023)
Background and Objectives: The traditional approach in managing wide cleft lip deformities involves presurgical nasoalveolar molding (NAM) therapy followed by surgical cleft lip repair between three and six months of age. This institution has implemented an early cleft lip repair (ECLR) protocol where infants undergo primary cleft lip repair between two and five weeks of age without NAM. This study aims to present this institution’s ECLR repair protocol over the past eight years from 188 consecutive patients with unilateral or bilateral CL/P deformity. Materials and Methods: Retrospective review was conducted at Children’s Hospital Los Angeles evaluating patients who underwent ECLR before three months of age and were classified as American Society of Anesthesiologists (ASA) class I or II from 2015–2022. Anthropometric analysis was performed, and pre- and postoperative photographs were evaluated to assess nasal and lip symmetry. Results: The average age at cleft lip repair after correcting for gestational age was 1.0 ± 0.5 months. Mean operative and anesthetic times were 120.3 ± 33.0 min and 189.4 ± 35.4, respectively. Only 2.1% (4/188) of patients had postoperative complications. Lip revision rates were 11.4% (20/175) and 15.4% (2/13) for unilateral and bilateral repairs, respectively, most of which were minor in severity (16/22, 72.7%). Postoperative anthropometric measurements demonstrated significant improvements in nasal and lip symmetry (p < 0.001). Conclusions: This analysis demonstrates the safety and efficacy of ECLR in correcting all unilateral cleft lip and nasal deformities of patients who were ASA classes I or II. At this institution, ECLR has minimized the need for NAM, which is now reserved for patients with bilateral cleft lip, late presentation, or comorbidities that preclude them from early repair. ECLR serves as a valuable option for patients with a wide range of cleft severity while reducing the burden of care.